Image data compression by using multiwavelete for color image (Baghdad Science Journal, 2006)
There are many images you need to large Khoznah space With the continued evolution of storage technology for computers, there is a need nailed required to reduce Alkhoznip space for pictures and image compression in a good way, the conversion method Alamueja